2023
DOI: 10.3390/microorganisms11061441
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toxoplasmosis and COVID-19 in a Mexican Population

Abstract: SARS-CoV-2 is the causal agent of COVID-19; the first report of SARS-CoV-2 infection was in December 2019 in Wuhan, China. This virus has since caused the largest pandemic in history, and the number of deaths and infections has been significant. Nevertheless, the development of vaccines has helped to reduce both deaths and infections. Comorbidities such as diabetes, hypertension, heart and lung diseases, and obesity have been identified as additional risk factors for infection and the progression of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Another important result was that 2% of patients diagnosed with COVID-19 showed evidence of active T. gondii infection, which was assessed by IgM detection. In their study, Galván-Ramírez MdlL et al reported that, when analyzing 191 patients with COVID-19 by IgM detection, 13.6% were found to have an active T. gondii infection (17).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another important result was that 2% of patients diagnosed with COVID-19 showed evidence of active T. gondii infection, which was assessed by IgM detection. In their study, Galván-Ramírez MdlL et al reported that, when analyzing 191 patients with COVID-19 by IgM detection, 13.6% were found to have an active T. gondii infection (17).…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, among the 1,302 COVID-19 patients tested, 36 cases were identi ed with the presence of T. gondii by IgM detection. Finally, of the 533 patients with COVID-19 screened by PCR, 21 cases were found to have T. gondii (Table 1) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Considering all patients, approximately 43.26% were males and 49.41% were females.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, another study did not confirm a strong association between T. gondii infection and susceptibility to COVID‑19 [ 21 ]. In a recent study in the Mexican population, the prevalence of IgG and IgM anti -Toxoplasma antibodies was demonstrated in 27.34% and 13.6% of COVID-19 patients, respectively [ 31 ]. A study conducted on the Czech and Slovak populations showed that toxoplasmosis is not considered a risk factor for COVID-19 and Toxoplasma -infected patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering recent studies of cases of breakthrough infection after the COVID vaccine the reported data about disease severity recorded 27% of asymptomatic cases, with the need for hospitalization in ten percent; it seems that toxoplasmosis in our research affected the severity of disease and death rate recorded 27 . However, other factors may be responsible for mild cases observed; one important factor is the emergence of the Omicron variant, characterized by its unparalleled transmission rate, heightened immune evasion, transmissibility, and reduced pathogenicity 28 , 29 . Breakthrough infections could be attributed to other factors, including characteristics of immunity, host determinants (such as age, comorbidities, immune status, and use of immunosuppressive drugs 30 .…”
Section: Discussionmentioning
confidence: 99%